THE ROLE OF HADITH CRITICISM IN EARLY ISLAMIC SCHOLARSHIP: METHODOLOGIES AND DEBATES (Al-Aasar, 2025)
The science of Hadith criticism occupies a pivotal position in early Islamic scholarship, serving as a crucial tool for safeguarding the authenticity of the Prophet Muhammad's (peace be upon him) sayings and actions. This paper explores the intellectual rigor, methodological principles, and scholarly debates that shaped Hadith criticism during its formative centuries. Early Muslim scholars, such as Imam al-Bukhari, Imam Muslim, and others, employed a meticulous verification process, examining both the chain of narrators (isnad) and the textual content (matn) of Hadith reports. The isnad analysis focused on the reliability, memory, and moral integrity of narrators, establishing stringent biographical evaluation methods (al-jarh wa al-ta’dil). Simultaneously, matn criticism ensured consistency with established Islamic principles and other verified narrations.This study highlights how differing schools of thought within Islam—such as the Ahl al-Hadith and Ahl al-Ra'y—engaged in debates over the scope and application of Hadith criticism. While some scholars prioritized strict adherence to the isnad, others introduced rationalist frameworks to assess textual coherence and theological soundness. Furthermore, the research examines how these early debates influenced the compilation of canonical Hadith collections and contributed to the development of Islamic jurisprudence (fiqh).Through critical engagement with primary sources and historical accounts, this paper underscores the intellectual diversity and methodological sophistication characterizing early Hadith studies. The findings reveal that Hadith criticism was not merely a tool for authentication but a dynamic scholarly enterprise reflecting broader epistemological concerns in early Islam. Ultimately, this exploration sheds light on the lasting impact of Hadith criticism on the preservation, interpretation, and transmission of Islamic knowledge.